Aktivitas Bagian Tumbuhan Sirih Hutan (Piper aduncum Linnaeus) yang Berasal dari Lokasi Berbeda dalam Menekan Pertumbuhan Colletotrichum gloeosporioides secara Invitro: english - Kumalasari, Lisa; Sulyanti, Eri; Hamid, Hasmiandy (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
The boiled water of Leaves and inflorescences of spiked pepper (Piper aduncum) is one alternative to control the pathogen of anthracnose (Colletotrichum gloeosporioides) in chili. The purpose of this study was to determine the activity of leaves and inflorescences of spiked pepper from different locations in suppressing the growth of C. gloeosporioides in vitro. The research was carried out in Phytopathology Laboratory of Pests and Plant Diseases Department, Faculty of Agriculture, Universitas Andalas from March to May 2017. The study used a Completely Randomized Design (CRD) with 5 treatments and 5 replications. Data from observations were analyzed by ANOVA and LSD at the level of 5%. The parameters observed were the growth of fungal colony area, wet and dry weight, number of conidia/ml of suspension and conidia germination. The results showed that the application of leaves and inflorescences of spiked pepper from different locations could suppress the growth of C. gloeosporioides in chili in vitro. Boiled water of inflorescences of spiked pepper from Bukit Lampu - Bungus - Padang City became the best treatment because it had the highest ability in suppressing C. gloeosporioides colony area with an effective suppression of 73.5% and reducing the highest germination capacity with an effective suppression of 23.28%. Its ability to reduce wet and dry weight were not different from inflorescences boiled water from Limau Manis, then the ability to suppress the number of conidia was not significantly different from leaves and inflorescences boiled water from Bukit Lampu and Limau Manis.